OPTIMALISASI PASAL 14 AYAT (2) HURUF F PERATURAN GUBERNUR NOMOR 60 TAHUN 2016 TENTANG PENYIAPAN DAN MENDISTRIBUSIKAN BAHAN RAPAT ALAT KELENGKAPAN DEWAN DPRD PROVINSI LAMPUNG (Studi Pada Bagian Persidangan Sekretariat DPRD Provinsi Lampung) - Iskandar Agus; ISTIARINI DESSY (Universitas Bandar Lampung (UBL), 2022)
In Article 14 Paragraph (2) Letter F Governor's Regulation Number 60 of 2016 concerning Preparation and Distributing Materials for the Council's Apparatus Meeting (AKD), in carrying out its functions and authorities, DPRD establishes units called DPRD Auxiliaries and aims to: assisting DPRD to achieve work results and assisting DPRD's institutional performance in every policy-making, as a legal prerequisite for a regional regulation. The apparatus of DPRD is formed during the initial period of DPRD membership in accordance with the instructions of the Minister of Home Affairs and the statutory regulations that have been stipulated. The problem of this research is how to optimize Article 14 Paragraph (2) letter F of the Governor's Regulation Number 60 of 2016 concerning the preparation and distribution of materials for the DPRD's board fittings (AKD) meeting in Lampung Province. The research method uses a normative juridical approach and an empirical approach using secondary data and primary data, then qualitative juridical data analysis is carried out. The results of the study, that the preparation and distribution of meeting materials for board equipment, especially in the Secretariat Session of the DPRD Lampung Province has not been maximized. The implementation of the duties and functions of the SessionDivision, such as the preparation of meeting minutes, preparation of trial administration, as well as the preparation of meeting resumes and reports on the results of board meetings are also considered to have not been maximally implemented efficiently and effectively, so it is necessary to optimize the quality of human resources and knowledge regarding the preparation of meeting materials. The completeness of the DPRD board and also the DPRD's equipment requires a harmonious synergy between the executive and the legislature so that in the discussion of the draft regional regulation it can provide benefits to the community..